The Role of the Single Incision Laparoscopic Approach in Liver and Pancreatic Resectional Surgery - Chatzizacharias, N.A.; Dajani, K.; Koong, J.K.; Jah, A. (Hindawi Publishing Corporation, 2016)
Introduction. Single incision laparoscopic surgery (SILS) has gained increasing support over the last few years. The aim of this narrative review is to analyse the published evidence on the use and potential benefits of SILS in hepatic and pancreatic resectional surgery for benign and malignant pathology. Methods. Pubmed and Embase databases were searched using the search terms “single incision laparoscopic”, “single port laparoscopic”, “liver surgery”, and “pancreas surgery”. Results. Twenty relevant manuscripts for liver and 9 for pancreatic SILS resections were identified. With regard to liver surgery, despite the lack of comparative studies with other minimal invasive techniques, outcomes have been acceptable when certain limitations are taken into account. For pancreatic resections, when compared to the conventional laparoscopic approach, SILS produced comparable results with regard to intra- and postoperative parameters, including length of hospitalisation and complications. Similarly, the results were comparable to robotic pancreatectomies, with the exception of the longer operative time reported with the robotic approach. Discussion. Despite the limitations, the published evidence supports that SILS is safe and feasible for liver and pancreatic resections when performed by experienced teams in the tertiary setting. However, no substantial benefit has been identified yet, especially compared to other minimal invasive techniques.